Raman spectroscopy in quality control of Chinese herbal medicine - Ao, Hui (2019)
Background: Chinese herbal medicine (CHM) is of noteworthy international interest due to its potential impact on healthcare and manifests numerous opportunities for new drug development. However, solid scientific evidence is still lacking regarding the safety, efficacy, and quality of CHM-derived medicines. Success in the modernization and globalization of CHM is heavily dependent on the achievements in advanced analytical techniques for in-line checks of CHM quality. Raman spectroscopy has become increasingly valued as an analytical technique in the pharmaceutical sector because it can provide a detailed chemical fingerprint. However, earlier research suggests that inadequate attention has been paid to the applications of Raman spectroscopy in CHM. Methods: Chinese and English literatures were reviewed via PubMed and Medicine databases, and through manual searches using keywords including traditional Chinese medicines, herbs, quality control, and Raman spectroscopy. Results: Applications of Raman spectroscopy in various aspects of CHM, including the identification and analysis of raw materials, in-line checks of formulation, characterization of adulterants, and detection of counterfeits, were reviewed systematically. Conclusion: An updated systematic review of the published literature has been conducted to analyze the most important milestones and latest achievements in this topic. Raman spectroscopy is playing an increasingly important role in the quality control of CHM and effectively promotes the modernization of CHM.